Upaya dalam Mencegah Perilaku Bullying dengan Pendekatan Pembelajaran Kolaboratif pada Siswa SMP Negeri 35 Medan - Bartolomeus Marulitua Simanjorang; Daniel R. Sihite; Lestari Lumban Batu; Putri Lopiga Br. Tarigan; Nadira Zawani; Stefy Margaretha; Kezia Thasa Emteta Karina Br. Bangun (International Forum of Researchers and Lecturers, 2024)
Bullying in the school environment is a problem that has a serious impact on students' emotional, social and academic development. This research aims to analyze efforts to prevent bullying behavior through a collaborative-based Pancasila and Citizenship Education (PPKn) learning approach for students at SMP Negeri 35 Medan. This research uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The research subjects were PPKn teachers and students in grades VII and VIII of SMP Negeri 35 Medan. The research results show that collaborative-based Civics learning is effective in increasing students' awareness about the impact of bullying and strengthening positive social relationships between them. Supporting factors for implementing this method include teacher support, student enthusiasm, and school policies, while inhibiting factors include time constraints and students' lack of initial understanding about collaboration. The results of this research show that the collaborative learning approach in Civics is able to create a safe and inclusive learning environment, while preventing bullying behavior. This research recommends further development of collaborative methods involving learning technology to strengthen the results achieved.